Пошаговое объяснение:
а) 4у+4у=64
8у=64:8
у=8
4•8+4•8=64
b)25x+52=102
25x=102-52
25x=50
x=50:25
x=2
25•2+52=102
c) (x+24)-15=52
x+24=52+15
x+24=67
x=67-24
x=43
(43+24)-15=52
d)125-(45+y)=39
45+y=125-39
45+y=86
y=86-45
y=41
125-(45+41)=39
3(x+4y)-4x=2(2x+y)
3x+12y-4x-2*(2x+y)=0
-x+12y-(4x+2y)=0
-5x+12y-2y=0
-5x+10y=0
y=0.5x
7(x-5у)+6x=3(x+4y)+27
7(x-5*(0.5x))+6x=3(x+4*(0.5x))+27
7*(x-2.5x)+6x-3*(x+4*0.5x)-27=0
7*(-1.5x)+6x-3*(x+4*0.5x)-27=0
-10.5x+6x-3*(x+4*0.5x)-27=0
-4.5x-3*(x+4*0.5x)-27=0
-4.5x-3*3x-27=0
-4.5x-9x-27=0
-13.5x-27=0
x=-27/13.5
x=-2
3(x+4y)-4x=2(2x+y)
3(-2+4y)-4*(-2)=2(2*(-2)+y)
-6+12y-4*(-2)-2*(2*(-2)+y)=0
-6+12y-(-4*2)-2*(2*(-2)+y)=0
-6+12y+8-2*(2*(-2)+y)=0
2+12y-2*(2*(-2)+y)=0
2+12y-2*(-4+y)=0
2+12y-(-8+2y)=0
2+12y+8-2y=0
10+12y-2*y=0
10+10y=0
y=-10/10
y=-1
ответ: x=-2; y=-1.
на фото, без проверки потому что там изи